2016
DOI: 10.5625/lar.2016.32.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a mouse model of 70% lethal dose by total-body irradiation

Abstract: Whereas increasing concerns about radiation exposure to nuclear disasters or side effects of anticancer radiotherapy, relatively little research for radiation damages or remedy has been done. The purpose of this study was to establish level of LD70/30 (a lethal dose for 70% of mice within 30 days) by total-body γ irradiation (TBI) in a mouse model. For this purpose, at first, 8-week-old male ICR and C57BL/6N mice from A and B companies were received high dose (10, 11, 12 Gy) TBI. After irradiation, the body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…For example, immunological responses to radiation and radiation combined injury were recently studied in CD-1 mice (an outbred strain from Charles River), since the genetic composition of an outbred strain may be more comparable to the human response (Tajima et al 2013). In addition, a study done comparing ICR (outbred) and C57BL/6N mice found that the radiation-induced mortality seen for the inbred mice was generally higher than what was observed for the outbred strain (Ryu et al 2016).…”
Section: Mouse Strainmentioning
confidence: 99%
“…For example, immunological responses to radiation and radiation combined injury were recently studied in CD-1 mice (an outbred strain from Charles River), since the genetic composition of an outbred strain may be more comparable to the human response (Tajima et al 2013). In addition, a study done comparing ICR (outbred) and C57BL/6N mice found that the radiation-induced mortality seen for the inbred mice was generally higher than what was observed for the outbred strain (Ryu et al 2016).…”
Section: Mouse Strainmentioning
confidence: 99%
“…United Nations Scientific Committee on the Effects of Atomic Radiation classifies LDR as any radiation dose below 100 mGy [29]. High dose radiation varies significantly ranging between 2000 mGy and 15 000 mGy [30][31][32][33]. High doses are usually accumulated during multiple exposures rather than a one-time whole-body exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Several conventional radiobiology studies have shown the loss of body weight along with the loss in most of the organ weight during the first initial days post-irradiation in non-lethal to sub-lethal cases 48 51 . However, our result shows the damages only to hematopoietic system organ due to the local radiation exposure to bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborated with the cell counts of spleen and thymus which shows continuous loss in cell number in this group upto 10th day post irradiation and beyond that restoration process started with full recovery at 30th day post irradiation. Several conventional radiobiology studies have shown the loss of body weight along with the loss in most of the organ weight during the first initial days post-irradiation in non-lethal to sub-lethal cases [48][49][50][51] . However, our result shows the damages only to hematopoietic system organ due to the local radiation exposure to bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%